A construction of Ag-modified raspberry-like AgCl/Ag2WO4 with excellent visible-light photocatalytic property and stability. (June 2018) - Xu, Hui; Cao, Yali; Xie, Jing; Hu, Jindou; Li, Yizhao; Jia, Dianzeng
Graphical abstract: An Ag-modified raspberry-like AgCl/Ag2 WO4 composite photocatalyst was fabricated via a facile solvent-free reaction technique. Highlights: The Ag-modified raspberry-like AgCl/Ag2 WO4 photocatalysts were prepared by a facile solvent-free method. Ag and AgCl were easily deposited on the Ag2 WO4 by one-step solid-sate reaction between Ag2 WO4 and HONH3 Cl. The morphology of raspberry-like can facilitate the contact of dye molecules and composite photocatalysts. The photocatalysts exhibit an effective separation of the photoinduced electron-hole pairs. The photocatalysts show excellent photocatalytic activity and photo-stability under visible light irradiation. Abstract: A novel multiphase photocatalyst of Ag-modified raspberry-like AgCl/Ag2 WO4 composite was successfully fabricated via a facile solvent-free reaction technique, in which the Ag and AgCl were subtlely generated from the one-step reaction between Ag2 WO4 particles and HONH3 Cl as reductant and chlorine source at room temperature. The as-obtained ternary Ag-modified raspberry-like AgCl/Ag2 WO4 composites can facilitate the contact of dye molecules and photocatalysts, exhibiting superior photocatalytic property and good recycling ability towards the decomposition of organic dye under the visible-light irradiation. The reductant addition amounts greatly affect the performance of Ag2 WO4 photocatalyst. The optimum composite ratio of Ag-modified AgCl/Ag2 WO4 samples show significant enhancement of visible-light photocatalytic activities and the degradation rate constant is about 16 times greater than that of pure Ag2 WO4 . The highly improved performance of Ag-modified raspberry-like AgCl/Ag2 WO4 structure can be ascribed to the surface plasma resonance (SPR) effects of metal Ag and the synergistic effect among composites, accordingly effectively promote the separation of photoinduced electron-hole pairs, widen the absorbance range in the visible light and increase surface area. The h + and ·OH degraded mechanism for the improved photocatalytic activity of Ag-modified AgCl/Ag2 WO4 is proposed based on radical-trapping experiments and ESR spectra records.